Laparotomy closure using an elastic suture: A promising approach. Issue 2 (5th June 2014) - Lambertz, A.; Vogels, R. R. M.; Busch, D.; Schuster, P.; Jockenhövel, S.; Neumann, U. P.; Klinge, U.; Klink, C. D.
Abstract Background: Midline laparotomy wound failure like burst abdomen remains one of the major complications after abdominal surgery. The use of sutures with a closer resemblance to abdominal wall physiology, like elastic threads, could decrease the risk of these complications occurring. Thus, we evaluated the possibility of using a new elastic thread composed of thermoplastic polyurethane (TPU) as a suture for the closure of midline laparotomies compared to conventionally used polypropylene (PP) in a rabbit model. Methods: The elastic TPU thread was processed and tensile tests were performed. Twenty female chinchilla rabbits underwent midline laparotomy. They were randomized to a TPU and a PP group depending on the suture used for fascia closure. After 7 or 21 days, the abdominal walls were assessed macroscopically for wound healing complications and were explanted for histopathological investigation. Results: Tensile tests showed a mean elastic elongation of 55.5% and a sufficient material strength of the TPU thread. In animal experiments, there was no difference between the groups at 7 days; however, the TPU suture showed significantly less CD68 positive cells (p < 0.001) and a higher collagen I/III ratio (p = 0.011) than PP did after 21 days. The amount of apoptotic cells was significantly elevated in the TPU group (p = 0.007) after 21 days. No differences were found concerning granuloma size and number of Ki67‐positive cells. Conclusions: The newly developed TPU thread shows promising tensile characteristics. Midline laparotomy closure is feasible and safe in a rabbit model. Immunohistochemistry indicates similar biocompatibility and wound healing after implantation compared to PP after 21 days. To confirm these findings and to proof long‐term capability further studies need to be conducted. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 417–423, 2015.